Gendering the Field Towards Sustainable Livelihoods for Mining Communities - Lahiri-Dutt, Kuntala (Asia-Pacific Environment Monograph, 2011)
The chapters in this book offer concrete examples from all over the world to show how community livelihoods in mineral-rich tracts can be more sustainable by fully integrating gender concerns into all aspects of the relationship between mining practices and mine affected communities. By looking at the mining industry and the mine-affected communities through a gender lens, the authors indicate a variety of practical strategies to mitigate the impacts of mining on women's livelihoods without undermining women's voice and status within the mine-affected communities. The term 'field' in the title of this volume is not restricted to the open-cut pits of large scale mining operations which are male-dominated workplaces, or with mining as a masculine, capital-intensive industry, but also connotes the wider range of mineral extractive practices which are carried out informally by women and men of artisanal communities at much smaller geographical scales throughout the mineral-rich tracts of poorer countries.